Patents Consulting Use Potential for Determining the State of the Art. Analysis in Microgrids with Renewable Energy Sources (2017)
In this document, we aim to show how important patent research is for technological and scientific development. We expose some of the main characteristics of patents, as well as the advantages that these documents have over the most commonly used sources of information in research, such as scientific and professional papers. We also cover the International Patent Classification, which should be known if one hopes to extract any valuable information from patents. Finally, we put everything into practice with a case of study regarding microgrids in power systems, with high penetration of renewable energy sources. With this study case, we invite the reader to include patent consulting into his or her literature research habits.